Tolerability and safety of the new anti-obesity medications - Hainer, Vojtech; Aldhoon-Hainerová, Irena (Drug safety, 2014)
Worldwide obesity prevalence has nearly doubled since 1980. Due to numerous co-morbidities, obesity represents a serious health and socioeconomic problem worldwide. Pharmacotherapy should be an integral part of comprehensive obesity management. Drug therapy can assist in weight loss and its maintenance in those individuals who do not achieve appropriate weight loss through lifestyle interventions alone. After the withdrawal of sibutramine from the market in 2010, orlistat, a lipase inhibitor, was the only remaining prescription drug approved for the long-term treatment of obesity. In 2012, phentermine/topiramate extended-release (PHEN/TPM ER) combination and lorcaserin were approved by the US FDA as novel medications for long-term weight management. Three major phase III trials conducted with each drug confirmed their efficacy in terms of weight loss/maintenance and improvement of cardiometabolic risks. No head-to-head studies between the two new anti-obesity drugs have been carried out. However, in the existing studies PHEN/TPM ER had a superior weight loss profile to lorcaserin but the incidence of adverse effects was lower with lorcaserin. Both drugs were well-tolerated, and adverse events were modest in intensity, dose dependent, rather rare, and tended to decrease with the duration of treatment. Major safety concerns regarding PHEN/TPM ER include elevations in resting pulse rate, teratogenicity, mild metabolic acidosis, and psychiatric and cognitive adverse events. Valvulopathy, cognitive impairment, psychiatric disorders, and hypoglycemia represent major safety concerns for lorcaserin. Although existing trials have not demonstrated any significant issues with PHEN/TPM ER-induced heart rate elevation and lorcaserin-induced valvulopathy, all safety concerns should be seriously taken into account in patients treated with either of these novel anti-obesity medications.
Keywords: farmaceutická chemie; Bupropion; Naltrexone; Phentermine; naltrexon; Fructose; benzoxaziny; Drug-Related Side Effects and Adverse Reactions; topiramat; Topiramate; Obesity; lidé; Chemistry, Pharmaceutical; glukagonu podobný peptid 1; látky proti obezitě; Benzazepines; fruktosa; benzazepiny; Anti-Obesity Agents; Humans; bupropion; nežádoucí účinky léčiv; liraglutid; obezita; Benzoxazines; Glucagon-Like Peptide 1; Liraglutide; fentermin